Quantifying proximal patellar tendon changes during adolescence in elite ballet dancers, a 2-year study - Rudavsky, A.; Cook, J.; Docking, S. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Patellar tendon pathology appears to develop in young athletes. It is not known how this tendon develops through adolescence. This longitudinal study investigated proximal patellar tendon development during the adolescent growth spurt in young ballet dancers, and identified if puberty (estimated by maturity offset) had an effect on tendon development. Methods: 52 dancers (32 female and 20 male dancers, ages 11-18 at baseline) had ultrasound images of their tendons every 6 months for 2 years. Changes in tendon size (anterior-posterior diameter) on greyscale images and echogenicity, as quantified using ultrasound tissue characterization, were recorded each time. Maturity offset was calculated used to estimate peak height velocity (adolescent growth spurt). Results: Maturity offset did not affect effect tendon composition before peak height velocity, however after participants passed peak height velocity, maturity offset increased the composition of stable echopattern (p<0.05); a 4% differential increase in type I echopattern, indicative of normal tendon structure, and a decrease in type III echopattern (more disorganized echopattern) by 0.7% per year. Anterior-posterior thickness increased by 0.2mm/year (p<0.05) measured 2cm below the patella. Conclusions: Following peak height velocity, the proximal patellar tendon attachment increased in thickness and demonstrated a more stable echopattern representative of aligned fibrillar structure. Future research is required to further understand this normal maturation and the factors that support this process, with the aim of reducing the development of patellar tendon pathology in the adolescent jumping athlete.